2005
DOI: 10.1002/jcb.20407
|View full text |Cite
|
Sign up to set email alerts
|

Fast apoptosis and erythroid differentiation induced by imatinib mesylate in JURL‐MK1 cells

Abstract: We compare the effects of Imatinib mesylate (Glivec) on chronic myeloid leukemia derived cell lines K562 and JURL-MK1. In both cell lines, the cell cycle arrests in G(1)/G(0) phase within 24 h after the addition of 1 microM Imatinib. This is followed by a decrease of Ki-67 expression and the induction of apoptosis. In JURL-MK1 cells, the apoptosis is faster in comparison with K562 cells: the caspase-3 activity reaches the peak value (20 to 30 fold of the control) after about 40 h and the apoptosis proceeds to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…We have previously shown that Imatinib mesylate treatment induces apoptosis in JURL-MK1 cells [Kuželová et al, 2005]. Figure 2 shows the kinetics of Imatinib-induced caspase-3 activation measured using the fluorogenic caspase-3 substrate (panel A) and apoptotic DNA fragmentation detected by TUNEL method (panel B).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that Imatinib mesylate treatment induces apoptosis in JURL-MK1 cells [Kuželová et al, 2005]. Figure 2 shows the kinetics of Imatinib-induced caspase-3 activation measured using the fluorogenic caspase-3 substrate (panel A) and apoptotic DNA fragmentation detected by TUNEL method (panel B).…”
Section: Resultsmentioning
confidence: 99%
“…1S). We have previously shown that imatinib mesylate induces apoptosis including a marked caspase‐3 activation and DNA fragmentation in JURL‐MK1 cells [Kuželová et al , 2005].…”
Section: Resultsmentioning
confidence: 99%
“…This compound induces cell cycle arrest followed by complete apoptosis including the mitochondrial apoptotic antigen 7A6 expression, caspases activation, and DNA fragmentation (20). Careful analysis of the effects of unlabeled caspase inhibitors z-DEVD-fmk and z-VAD-fmk on FLICA staining led us to conclude that, in our experimental system, the fluorescent signal of FLICA originates mainly, if not exclusively, from still unspecified sites that differ from the caspase active sites.…”
mentioning
confidence: 77%
“…Up to 30-fold increase in caspase-3 activity over the control values was observed in cell lysates using fluorogenic substrate Ac-DEVD-AFC, within 40-50 h following Imatinib addition (20). In the present work, we employed the fluorochromelabeled caspase-3 inhibitor FAM-DEVD-fmk (hereafter referred to as FLICA) to monitor the caspase activation in individual cells by means of flow cytometry.…”
Section: Kinetics Of Flica Labeling Correlates With Apoptosis Inductionmentioning
confidence: 99%